DEVELOPMENT OF AUTOMATION OF CONTROL OF LINEAR AND NONLINEAR CONTROL SYSTEMS AND NAVIGATION OF WATER TRANSPORTATION MEANS - Дакі, О. А.; Кривошей, Ф. О.; Панов, С. Л. (Science-based technologies, 2019)
It was shown that the equipment for control of the systems of navigation and navigation of water transport means includes an input stimulator (test signals) generator, a measuring device that allows determining the initial response of the control object to the input stimulus signal, the information processing device, and the registration device. Therefore, to form the input stimulating signal, it is expedient to use generators built on the method of converting code into an analogue. The purpose of the control automaton to determine the technical state of the systems of navigation and navigation of water transport vehicles is to make an opinion on the status of the object of control at the instantaneous values of the output signal at the time interval. It is shown that in the analyzer of discrete action, the measurement of the output signal of the control object is performed at fixed reference points using the converter analog code. The functional scheme of the multiplication device is presented together with the part of the control unit. The principle of work is considered. The versatility of the proposed control machine is achieved, firstly, by the possible change in the parameters of the generator of input signals, which allow the formation of signals of various forms, and, secondly, by the adjustment of the analyzer, which allows the processing of the output signal at different values. It is substantiated that in the control of arbitrary linear systems, you can use sinusoidal input signals and thus get rid of the need to rebuild the converter code-analogue and encoder, which greatly simplifies the circuit of the control machine. For the required accuracy with the number of system parameters for more than two input signals must consist of several sinusoidal signals of different frequencies. Changing the frequency of the input sinusoidal signal is provided by a frequency divider with a variable fission factor.